Phytochemical and anti-microbial potential of Mallotus mollissimus and Solanum erianthum extracts - Nurul Ain Ismail; Azlinah Matawali; Goh, Lucky Poh Wah; Lee, Ping Chin; How, Siew Eng; Jualang @Azlan Abdullah Gansau (Malaysian Society for Biochemistry and Molecular Biology, 2021)
Mallotus mollissimus (M. mollissimus) and Solanum erianthum (S. erianthum) plants have been reported to possess medicinal properties and have been effectively used by indigenous communities. However, the precise compositional and anti-microbial properties of these plants remain unclear. Hence, this study aims to investigate the qualitative phytochemicals and anti-microbial properties of the extract from M. mollissimus and S. erianthum. Anti-microbial activities and phytochemical studies were carried out using crude methanolic extract, chloroform fractions and selected chromatography fractions of M. mollissimus and S. erianthum. Anti-microbial activities targeting Gram-positive and Gram-negative bacteria were performed using the disk diffusion method at 100 mg/mL. M. mollissimus have superior anti-microbial activities as compared to S. erianthum where Streptococcus pneumoniae were inhibited by CE.F3 fraction of M. mollissimus with an average inhibition diameter of 7.0 mm ± 0.48. We qualitatively determined the alkaloids, steroids, and cardiac glycosides in both plant extracts using biochemical assays. Interestingly, flavonoids, terpenoids, and tannins were found in M. mollissimus, which were correlated to the inhibition of Streptococcus pneumoniae. These findings indicate that M. mollissimus and S. erianthum contains large phytochemicals which give rise to anti-microbial effects.